Chances and choices : exploring the impact of music education - Pitts, Stephanie (New York : Oxford University Press, 2012)
"In Chances and Choices, Stephanie Pitts surveys the aims and impact of formative musical experiences, evaluating the extent to which music education of various kinds provides a foundation for lifelong involvement and interest in music. Pitts draws upon rich qualitative data from her own extensive original study of over 100 adults with an active interest in music in the UK and Italy to address several key themes in the study of music education. Intertwined with discussion of topics such as music education policy and the role that music teachers and other role models play in nurturing musicians are first person 'interludes' that showcase the stories and voices of the research participants as they reflect upon the influences and opportunities that shaped their musical life histories. Pitts' analysis adds valuable context to these stories, illuminating the historical and contemporary debates about music education and proposing ways in which school music might better prepare young people for continued participation in music throughout their lives. A companion website contains Pitts' data sets and analytical frameworks; the website also features an interactive database through which readers can share their own musical life histories and search others that have been contributed there. Shedding new light on the long-term effects of music education, Chances and Choices is an important resource to understand how we can encourage lasting engagement with music and other cultural activities in every individual." -- p. [4] of cover and publisher's website.
Chances, choices and conclusions. Chances and choices in musical education ; The usefulness of life history approaches ; Recommendations and future directions -- Postlude -- Glossary.
Includes bibliographical references (p. 205-216) and index.
Keywords: Music -- Instruction and study -- Social aspects